2020
DOI: 10.1088/1361-6463/ab8fde
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed nanosecond air discharge in contact with water: influence of voltage polarity, amplitude, pulse width, and gap distance

Abstract: Plasma technology is a highly promising and advantageous technology for liquid processing. In air in-contact with water, plasma produces highly reactive species (ions, electrons, radicals, photons, etc) that diffuse into the water volume and initiate physical and chemical phenomena of interest, e.g. organic and inorganic pollutant degradation. In this study, we investigate the influence of basic parameters, such as voltage polarity, voltage amplitude, plasma lifetime, and air-gap distance, on the properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…It is clear that, as for the unipolar pulse mode, the polarity of pulse voltage has little effect on the excited state of active species production, and the emission intensities of those active species in unipolar positive NPG-LD are slightly higher than those in unipolar negative NPG-LD. The results are similar to the work of Hamdan et al [15] who reported that the concentration of gaseous reactive nitrogen and oxygen species produced by both unipolar positive and negative pulse polarities driven discharge in-contact with water is similar. However, under the same gas flow rate and pulse peak voltage, the intensities of N 2 (C), OH(A), and O(3p) emitted from bipolar NPG-LD are much higher than those of unipolar (both the positive and negative) NPG-LDs.…”
Section: Oes Characteristic Of the Npg-ldssupporting
confidence: 91%
See 1 more Smart Citation
“…It is clear that, as for the unipolar pulse mode, the polarity of pulse voltage has little effect on the excited state of active species production, and the emission intensities of those active species in unipolar positive NPG-LD are slightly higher than those in unipolar negative NPG-LD. The results are similar to the work of Hamdan et al [15] who reported that the concentration of gaseous reactive nitrogen and oxygen species produced by both unipolar positive and negative pulse polarities driven discharge in-contact with water is similar. However, under the same gas flow rate and pulse peak voltage, the intensities of N 2 (C), OH(A), and O(3p) emitted from bipolar NPG-LD are much higher than those of unipolar (both the positive and negative) NPG-LDs.…”
Section: Oes Characteristic Of the Npg-ldssupporting
confidence: 91%
“…Thagard et al [14] found that in the unipolar positive pulsed discharge, the production of H 2 O 2 relies on the solution pH, whereas in the unipolar negative pulsed discharge, the production of H 2 O 2 is lower and depends on the liquid conductivity. Hamdan et al [15] found that the change of the solution conductivity and pH, and concentrations of H 2 O 2 , -NO , 3 and -NO 2 are similar in both positive and negative polarity pulsed discharges. However, negative pulsed discharge has higher degradation rate of methylene blue, which is attributed to that the untreated solution at bottom can flow to the plasma-liquid interface at higher flow rate in negative pulsed discharge.…”
Section: Introductionmentioning
confidence: 99%
“…As is known from the literature [22,96], the shortening of the voltage pulses to submicrosecond range is an efficient way to prevent transition from streamer to spark, which is also valid for discharges with liquid electrodes. That is confirmed by spectroscopic measurements of the electron density in nanosecond pulsed pin-to-liquid discharges where the values of electron density are found to be in the order of 10 15 cm −3 [180]. The increase of the duration of the voltage pulse to the microsecond range allows the transition of the discharge from streamer to transient spark regime with the electron density values approaching 10 17 cm −3 [122,181,182].…”
Section: Electron Density 421 Optical Emission Spectroscopymentioning
confidence: 55%
“…The dominant method for temperature determination is optical emission spectroscopy of OH and N 2 emissions [83,100,115,122,123,173,[180][181][182][183][184][185][232][233][234][235][236]. Besides, rotational Raman spectroscopy [137,189,191,192], broadband UV absorption spectroscopy [231] and pressure broadening [100] were employed for the estimation of gas temperature in discharges in contact with liquids.…”
Section: Gas Temperaturementioning
confidence: 99%
See 1 more Smart Citation